Extreme Wave Loading on a Vertical Circular Cylinder - Shi Liu; Xinran Guo; Yi Yang; Yatao Lu; Lifen Chen (Applied Sciences, 2023)
Extreme wave loading on a marine structure, consisting of a quasi-static and a dynamically slamming component, often drives the design of such a structure. Their accurate predictions remain challenging tasks. This paper examines the slamming contribution to the force–time histories from a series of experiments in which the crest of a wave is forced to hit a truncated cylinder suspended from above. A range of inundation levels, representing the breaker heights, are considered. The work also provides insights into nonlinear load characteristics on a vertical truncated cylinder. A simple analytical model based on the Newtonian momentum analysis is extended to describe the scaling of the horizontal peak force with the inundation level, i.e., the relationship between the wave slamming loads and the breaker height. More specially, it is found that the peak horizontal impact force is proportional to the inundation level and the square of the linear wave amplitude. In addition, the horizontal and the vertical impact forces on a truncated cylinder are found to increase with the increasing inundation level, while the effect from the wave steepness is relatively small. Furthermore, the higher-order wave components driving nonlinear (quasi-static) loading on a structure are separated by applying a phase-based separation method assuming a Stokes-like approximation. The separation method is found to work well even for long shallow-water waves that have strong nonlinearities. The results suggested that the relative contribution from the fundamental linear wave and higher-order wave components decreases and increases with the increasing nonlinearity of long waves, respectively, characterized by the Ursell number. Finally, this increase in the higher-order wave components is found to be saturated at large Ursell numbers.